Studies on Growth Characteristics and Cross-Neutralization of Wild-Type and Delta SARS-CoV-2 From Hisar (India) - Khandelwal, Nitin; Chander, Yogesh; Kumar, Ram; Nagori, Himanshu; Verma, Assim; Mittal, Priyasi; T, Riyesh; Kamboj, Sameer; Verma, Sukhbir Singh; Khatreja, Subhash; Pal, Yash; Gulati, Baldev R.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has rapidly evolved to generate several antigenic variants. These variants have raised concerns whether pre-existing immunity to vaccination or prior infection would be able to protect against the newly emerging SARS-CoV-2 variants or not. We isolated SARS-CoV-2 from the coronavirus disease 2019 (COVID-19)-confirmed patients in the beginning of the first (April/May 2020) and second (April/May 2021) waves of COVID-19 in India (Hisar, Haryana). Upon complete nucleotide sequencing, the viruses were found to be genetically related with wild-type (WT) and Delta variants of SARS-CoV-2, respectively. The Delta variant of SARS-CoV-2 produced a rapid cytopathic effect (24–36 h as compared to 48–72 h in WT) and had bigger plaque size but a shorter life cycle (~6 h as compared to the ~8 h in WT). Furthermore, the Delta variant achieved peak viral titers within 24 h as compared to the 48 h in WT. These evidence suggested that the Delta variant replicates significantly faster than the WT SARS-CoV-2. The virus neutralization experiments indicated that antibodies elicited by vaccination are more efficacious in neutralizing the WT virus but significantly less potent against the Delta variant. Our findings have implications in devising suitable vaccination, diagnostic and therapeutic strategies, besides providing insights into understanding virus replication and transmission.